Enhancing Financial Report Quality in Yogyakarta's Micro, Small, and Medium Enterprises (MSMEs) Through Information Technology Application and Organizational Commitment - Visnhu, Bartolomeus Galih (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
This study aims to understand the phenomenon where the information technology application and organizational commitment can contribute to enhancing financial report quality in Yogyakarta’s MSMEs. High-quality financial reports may serve as an effective platform for diverse parties to make economic decisions. MSMEs were chosen as the focus of the research because they often face challenges in terms of access to capital for their business expansion, caused by suboptimal capital distribution. This insufficient capital distribution is largely due to a lack of sufficient information for investors regarding the conditions of MSMEs. A quantitative research approach was used, involving the distribution of questionnaires and obtaining 209 responses from MSME operators in Yogyakarta, followed by hypothesis testing using PLS-SEM. The findings indicate that the information technology application improves the financial report quality. Furthermore, Organizational commitment acts as a moderator in enhancing the link between the deployment of IT and the quality of financial reports. Ultimately, the results of this study can provide practical contributions to organizations, particularly MSMEs, in improving their financial report quality through the implementation of information technology and organizational commitment.